Effect of Input-Output (IO) Buffering to Minimize Flow Control Blocking in Software Defined Networkinga - Lali, M. I.; Bilal, M. M.; Nawaz, M. S.; Deen, M.; Shahzad, B.; Khaliq, S. (The Nucleus, 2016)
Software Defined Networking (SDN) is a new network technology that tries to overcome the shortcomings and problems in traditional networks. By centralizing the network state in control layer, SDN architecture makes it easier to define and enforce consistent policies across the network. By separating data plane from control plane, dynamic requirements of complex networks can be easily manage through SDN. For future networks, SDN is already playing a significant role. SDN offers robustness, flexibility, vendor's independent platform and consistent policies across the network. In this article, we analyze different Input-Output (IO) buffering strategies which effect flow control blocking in SDN. We evaluate the performance of three different IO buffering strategies: single buffering, double buffering and ring buffering. Analyses of three IO buffering strategies are carried out in terms of two network parameters: latency and packet delivery ratio (PDR). Our results show that in terms of latency, ring buffering performs much better than single and double buffering for varying number of hosts and switches in a network. Furthermore, PDR is significantly minimized by use of buffers during network congestion in SDN.